An Investigation of the Electrical Beauty Products Category for Boots.com - Lall, Manjit; Dhage, Seemit; Gupta, Rahul; Manjee, Rizwan (2007)
The team of four MBA students were invited into Boots.com to investigate the performance of the Electrical Beauty products category within their online business. Whilst in the very early stages of the project, the group was introduced to the McKinsey Retail Model which Boots.com was using. The model contained five elements - Range Authority, Expertise, Experience, Convenience and Price. Under this model, it was proposed that to excel, organisations needed to be Best in Class in two elements and not negative in the other three.